2006
DOI: 10.1128/jcm.44.3.916-922.2006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Feline Leukemia Virus RNA in Saliva from Naturally Infected Cats and Correlation of PCR Results with Those of Current Diagnostic Methods

Abstract: A novel diagnostic test for feline leukemia virus (FeLV) RNA in saliva from naturally infected cats is described in this study. We evaluated different diagnostic tests and compared them with the widely used enzyme-linked immunosorbent assay (ELISA) for the detection of p27 in the diagnosis of FeLV. Blood samples from 445 cats were tested for the presence of provirus by real-time PCR and plasma and saliva specimens from those cats were tested for the presence of viral RNA by real-time reverse transcription (RT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
3
3

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 17 publications
4
59
3
3
Order By: Relevance
“…A similar correlation was found by Tandon et al (2005). Consistent with other investigators, we identified 22 samples which had detectable, albeit low, viral DNA levels and undetectable viral RNA (Tandon et al, 2005;Gomes-Keller et al, 2006a;Gomes-Keller et al, 2006b;Hofmann-Lehmann et al, 2006). Several possible explanations for discordant RNA and DNA qPCR results exist.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A similar correlation was found by Tandon et al (2005). Consistent with other investigators, we identified 22 samples which had detectable, albeit low, viral DNA levels and undetectable viral RNA (Tandon et al, 2005;Gomes-Keller et al, 2006a;Gomes-Keller et al, 2006b;Hofmann-Lehmann et al, 2006). Several possible explanations for discordant RNA and DNA qPCR results exist.…”
Section: Discussionsupporting
confidence: 79%
“…The finding of previously covert viral DNA in some cats which ostensibly totally resisted FeLV infection was not restricted to FeLV-61E-A, as other investigators found a similar phenomenon in cats challenged with the FeLV-A/Glasgow-1 Flynn et al, 2002;Tandon et al, 2005;Cattori et al, 2006;Gomes-Keller et al, 2006a;Gomes-Keller et al, 2006b;. It remained unknown, however, whether the viral DNA we detected by our qPCR assay represented intact, replication-competent provirus or replication-defective viral DNA sequences.…”
Section: Introductionmentioning
confidence: 38%
See 1 more Smart Citation
“…PCR is being used currently for detection of viral nucleic acid (RNA or proviral DNA) and is highly strain specific. PCR positive for FeLV proviral DNA indicates the presence of exogenous but not necessarily can be used as a diagnosis for viremia (Gomes-Keller et al, 2006). In these cases the RT-PCR detects the presence of viral RNA and informs the development of viremia in infected animals, but current reagents and testing protocols should be well standardized.…”
Section: Diagnosis and Management Of Felv-infected Catsmentioning
confidence: 99%
“…Recommend annual retesting after any discordant test result until agreement. A positive test doubtful a healthy animal, it should be done further confirmatory tests such as direct immunofluorescence and PCR for provirus (Gomes-Keller et al, 2006;Hartmann, 2006;Lutz et al, 2009). …”
Section: Diagnosis and Management Of Felv-infected Catsmentioning
confidence: 99%